Gestão de riscos de preços na cafeicultura: uma proposta para agentes da cadeia produtiva - Ferreira, João Batista (2022)
The present research aims to identify the use of operations in the futures market and in the options market in the management of price risks in the coffee production chain, understanding Brazilian and international experiences in price risk management and the practices adopted by agents of the production chain, in the Triângulo Mineiro and Alto Paranaíba region, and propose a model. For this, the study has an exploratory nature, qualitative and quantitative and is based on field and documentary research. The methodological procedure adopted in this research seeks in the integrative review to build a conceptual structure, being the basis for the proposed Price Risk Management Model in Coffee Growing. In order to portray coffee price risk management practices, the foundations of the Theory of Practice were adopted, specifically Strategy as Practice. As a result, in relation to the consultation on Brazilian and international experiences of agricultural price risk management, it is concluded that the use of put options by the Mexican government and the models: "Leading Company + Futures" and "Futures + Insurance" , from the Dashang Research Institute, in China, are relevant experiences and models of price risk management. By highlighting the price risk management practices adopted by agents in the production chain in the Triângulo Mineiro and Alto Paranaíba region, it is concluded that cooperatives are important as intermediaries in the coffee commercialization processes and in supporting the acquisition of inputs by coffee growers. As well as, it provided the opportunity to know the strategy as a social practice, through the daily activities of the practitioners and their action in the researched cooperatives. Regarding the proposed price risk management model, based on the experiences found in the literature and on the practices carried out in the studied regions, it was verified that the model is viable and feasible, whether carried out through cooperatives, government policies and/or as a investment fund. With the basic purpose of price insurance, through put options, unlinked from the commercialization processes. It is concluded that risk mitigation, especially coffee price risks, has become relevant to the success of agricultural businesses, due to factors impacting production, income and results. Agricultural derivatives play an important role in the management of risks involving the commercialization of products, whether in the purchase of inputs or in the sale of production.